2013
DOI: 10.1007/s12010-013-0481-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Chlorella vulgaris on Sugarcane Vinasse: The Effect of Anaerobic Digestion Pretreatment

Abstract: Microalgae farming has been identified as the most eco-sustainable solution for producing biodiesel. However, the operation of full-scale plants is still limited by costs and the utilization of industrial and/or domestic wastes can significantly improve economic profits. Several waste effluents are valuable sources of nutrients for the cultivation of microalgae. Ethanol production from sugarcane, for instance, generates significant amounts of organically rich effluent, the vinasse. After anaerobic digestion tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 33 publications
(40 reference statements)
1
30
0
8
Order By: Relevance
“…Barrocal et al (2010) showed that, in batch culture, Spirulina maxima was able to grow on Schlösser medium containing up to 5.0 g/L of diluted beet vinasse, reaching biomass concentrations between 3.5 to 4.8 g/L. The vinasse concentration applied in this study was similar to that used in Marques's (2013), where vinasse concentration was 2.0 g/L and biomass concentration was 0.7 g/L in a 10 days batch. In this study, the biomass concentration was equivalent when the equivalent percentage of vinasse was used.…”
Section: Ccd Studiessupporting
confidence: 56%
See 1 more Smart Citation
“…Barrocal et al (2010) showed that, in batch culture, Spirulina maxima was able to grow on Schlösser medium containing up to 5.0 g/L of diluted beet vinasse, reaching biomass concentrations between 3.5 to 4.8 g/L. The vinasse concentration applied in this study was similar to that used in Marques's (2013), where vinasse concentration was 2.0 g/L and biomass concentration was 0.7 g/L in a 10 days batch. In this study, the biomass concentration was equivalent when the equivalent percentage of vinasse was used.…”
Section: Ccd Studiessupporting
confidence: 56%
“…Treatment of beet vinasse using a vinasse concentration of 5 g/L (supplemented with Schlösser medium) pre-treated anaerobically using the microalgae Spirulina maxima resulted in a production of 4.8 g/L of biomass in eleven days (Barrocal et al 2010). Marques (2013) worked on diluted vinasse treatment (2 gCOD/L) using C. vulgaris and obtained 0.49 g/L in seven days. There is currently no information on specific studies related to the use of Scenedesmus sp to treat this effluent.…”
Section: Introductionmentioning
confidence: 99%
“…The use of digestate vinasse was used to cultivate the microalgae Chlorella vulgaris (Marques et al, 2013;Candido and Lombardi, 2017) and Neochloris oleoabundans (Olguín et al, 2015). Initially, research shows that vinasse was highly toxic to C. vulgaris at concentrations greater than 4%, reaching allowable concentrations of about 8.6% after treatment (Marques et al, 2013). C. vulgaris, a widely used species in accumulation of valuable microbial lipids (Reis et al, 2014b), was able to achieve specific growth rates of 0.76 day ) (Marques et al, 2013).…”
Section: Ad Of Vinasse: Operation Energy Generation and Digestate Usementioning
confidence: 99%
“…Initially, research shows that vinasse was highly toxic to C. vulgaris at concentrations greater than 4%, reaching allowable concentrations of about 8.6% after treatment (Marques et al, 2013). C. vulgaris, a widely used species in accumulation of valuable microbial lipids (Reis et al, 2014b), was able to achieve specific growth rates of 0.76 day ) (Marques et al, 2013). The use of AD can represent a feasible opportunity for making vinasse an appropriate cultivation medium for microbial cultivation, such as in the use of fungi with resilience to unfavorable conditions of growth (Reis et al, 2014a).…”
Section: Ad Of Vinasse: Operation Energy Generation and Digestate Usementioning
confidence: 99%
“…Currently, the algae used in the cultivation of the stillage medium are: Chlorella vulgaris [5][6][7], Chlorella sp. Bejerinck [8], Chlorella sorokiniana [9], Chlamydomonas reinhardii [10], Tetraselmis suecica [8], Scenedemsus sp.…”
Section: Introductionmentioning
confidence: 99%